Beginning teacher agency in the enactment of fundamental British values: a multi-method case study. (2nd November 2019) - Bamber, Philip; Bullivant, Andrea; Clark, Alison; Lundie, David
ABSTRACT: There has been significant discussion and debate about the meaning and implementation of the requirement for schools to promote fundamental British values. While much of the research in this area focuses on surveying teachers' attitudes, this paper set out to understand the processes of professional enactment through which beginning teachers interpret the policy agenda across sites and contexts in initial teacher education. A multi-method case study was undertaken at a large provider of initial teacher education in the North of England, following beginning teachers on project placement in primary schools. Theorising awareness and agency as axes of professional formation, the paper identifies three key thematic foci: community partnership; the treatment of inclusiveness and diversity; and the professional understanding, interpretation and performance of value language. Context shapes enactment of each theme, with reflective space for criticality required if beginning teachers are to develop professional agency with regard to their role as values educators. This is a feature of the culture of placement schools, and while university-based teaching can ameliorate the effects of unreflective compliance, it cannot provide a replacement for professional acculturation. The paper explores the implications of reflection on enactment for the professional acculturation of beginning teachers, making recommendations for teacher education.